Impact of Financial Technology (FinTech) on Accounting Efficiency and Supply Chain Performance in Nigeria’s Logistics Sector (American Journal of Smart Technology and Solutions, 2025)
Using annual time-series data between 2000 and 2024, the study follows an Autoregressive Distributed Lag (ARDL) modeling strategy to estimate both short-run dynamics and long-run relationships between Financial Technology (FinTech), Accounting Efficiency and Supply Chain Performance within Logistics Sector in Nigeria. The value of electronic financial transactions is used as a proxy of FinTech adoption, financial reporting quality indices as a proxy of accounting efficiency, and composite logistics indicators as a proxy of supply chain performance. Descriptive analysis shows that there is a lot of variation in FinTech uptake but not much variation in accounting practices. Cointegration of the variables is supported by the ARDL bounds test. The long-run estimates show that the efficiency of FinTech and accounting have a statistically significant positive impact on logistics performance, with coefficients of 0.42 and 0.35, respectively. In the short-run, the efficiency gains of accounting have an immediate effect, and the benefits of FinTech are felt in a more long-term way. The error correction term implies a high rate of convergence to equilibrium (adjustment speed of 45%). Model robustness is validated by diagnostic tests. The results suggest that FinTech usage and effective financial management are mutually supportive factors of supply chain efficiency in Nigeria. Based on this, companies and policy makers ought to intensify the use of digital financial instruments and enhance accounting functions to promote robust and competitive logistics systems.